2021
DOI: 10.3389/fpsyg.2021.720717
|View full text |Cite
|
Sign up to set email alerts
|

An Encounter With the Other: A Thematic and Content Analysis of DMT Experiences From a Naturalistic Field Study

Abstract: Introduction:N,N-dimethyltryptamine (DMT) is an endogenous serotonergic psychedelic capable of producing radical shifts in conscious experience. Increasing trends in its use, as well as new trials administering DMT to patients, indicate the growing importance of a thorough elucidation of the qualitative content, over and above structure, which the drug occasions. This is particularly in light of the hyper-real, otherworldly, and often ontologically challenging yet potentially transformative, nature of the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(72 citation statements)
references
References 63 publications
4
68
0
Order By: Relevance
“…The results of this study contribute to the limited descriptive information about inhaled N , N -DMT use and the resultant experience 11 , 30 , 43 . This study identified a reported median dose of inhaled N , N -DMT of 40 mg and duration of experience of 10 min.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The results of this study contribute to the limited descriptive information about inhaled N , N -DMT use and the resultant experience 11 , 30 , 43 . This study identified a reported median dose of inhaled N , N -DMT of 40 mg and duration of experience of 10 min.…”
Section: Discussionmentioning
confidence: 82%
“…Early but growing efforts attempt to characterize the phenomenological experience following exogenous DMT administration 2 , 5 , 16 – 30 . Common emerging themes include mystical-type experiences 21 ; transcendence and connectedness 2 ; increased noesis (ascertaining direct or intuitive knowledge) 31 , 32 ; alterations in consciousness and the sense-of-self 2 , 17 , 21 ; vivid imagery and perceptual changes 16 , 24 ; emotional effects 16 ; death and rebirth 2 ; the divine, spirituality, and religiosity 2 , 21 ; and encounters with autonomous entities and beings 5 , 27 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations